Theoretical aspects of professional competence of teachers of fine arts (Pedagogy of Higher and Secondary Education, 2012)
Fursikovа T. Theoretical aspects of professional competence of teachers of fine arts.The article analyzes the concept, contents and elements of professional competence of teachers of fine arts.
Keywords: fine art; teacher; professional competence